THE PREVALENCE AND RISK FACTORS OF OTIC BAROTRAUMA AMONG AIRCREW MEMBERS: Pharmaceutical Science-Medicine - SULTAN, INTESSAR; KHALID KHAYAT, SHAHAD; REDHA GAROUT, IBTIHAL; SHAKER ALAHMADI, LAYAN; AHMAD ALI ALZAHRANY, ABDLAZIZ (International Journal of Life Science and Pharma Research, 2019)
Barotrauma is the most prevalent medical problem associated with airplane travel (traveling) and has been a causal factor in the aviation accident. This study aimed to explore the prevalence of otic barotrauma and its risk factors among the aircrew members. This cross sectional study included 267 aircrew members (116 pilots and 151 flight attendants) who presented themselves to the outpatient clinic at “Saudi Airlines Medical Services” for assessment of their fitness before the flight. The participants were selected using a non-probability consecutive sample over the study period from January to September 2018. They were interviewed face to face about their socio-demographic and job characteristics, the risk factors for barotrauma, as well as the symptoms of ear trauma. Otic barotrauma was found in 39% and 14.4 % had repeated barotrauma. Increased odds ratios of barotrauma were detected among Saudis (OR 2.5 (95% CI: 1.4-4.4)) (p=0.002), smokers (OR 1.8 (95% CI: 1.13-3.1)) (p=0.015), pilots (OR 1.8 (95% CI: 1.1-2.9))(p=0.026), those with allergy (OR 2.6 (95% CI: 1.2-5.5)(p=0.012), members working for > 70 hours per month (OR 2.5 (95% CI: 1.5-4.2))(p=0.000), and in females with hormonal disturbance (OR 2.9 (955 CI: 1.2- 6.7)) (p=0.016) or on hormonal therapy (OR 2.6 (95% CI: 1.1- 6.4)) (p=0.028). 39% of aircrew members at Saudi airlines had ear barotrauma and 14.4% had repeated heart attacks. The risk of barotrauma was increased among pilots, Saudis, smokers, those with allergy or hormonal disturbance, or working for >70 hours/month. We recommend to limit smoking on flights, decrease total hours of duties <70 per month (especially for pilots), and to do regular ENT exam for all aircrew members.